Designing Air-Cored Axial Flux Permanent Magnet Generator with Double Rotor - Aji Nur Widyanto; Rahmat Ariwidayat; Faiz Husnayaian; Amien Rahardjo; Agus R Utomo; I Made Ardita (ELKHA : Jurnal Teknik Elektro, 2022)
The development of renewable energy is carried out to reduce the use of fossil energy, which is decreasing in existence, increasing in price, and having a very long recovery cycle. One of the uses of technology to support renewable energy development is a synchronous machine that can be used to utilize wind and water energy. One type of synchronous machine that is widely used today is the radial flux machine. However, there is a saturation point in their development. Axial flux machines also called disc type machines, are an alternative to radial flux machines due to their compact shape and high-power density. Axial flux machines can be operated as small to medium-scale power plants. Besides that, they are ideal for low-speed applications. An axial flux permanent magnet (AFPM) generator is designed and built in this study. This generator design consists of a dual rotor with twelve permanent magnets and a single stator with nine coils. The primary material used for the stator and rotor is acrylic, while the permanent magnet uses neodymium N52. It is necessary to know the stator and rotor parameters such as distribution factor (kd), pitch factor (kp), and winding factor (kw) for designing the AFMP generator. The AFPM generator is designed to produce a phase voltage of 4.03 V at a nominal speed of 500 r/min. Based on the measurement results, it was found that the phase voltages at a rotating speed of 500 r/min for each phase are VR = 2.94 V, VS = 2.97 V, and VT = 2.95 V. There are differences in the test results and the design. It can be caused by design simplicity that does not consider magnetic saturation and internal reactance, which cannot be ignored but is not included in the calculation.